Trekkers in the High-altitude Pyrenees: What Representation for Which Practice? - Radu Cristian Barna (Revue de Géographie Alpine)
This article paints a portrait of trekkers in the high-altitude Pyrenees. Sometimes depicted as different from the trekkers of the Alps, this image may stem from a different imaginary construct, be it in terms of a particular representation of the high-altitude Pyrenees, or of their practice. In order to better evaluate said aspects, we have conducted 25 interviews with professionals of the mountains, members of mountain associations, representatives of institutions and the trekkers themselves. As a follow-up, we have asked 166 trekkers to fill out a questionnaire and we have followed some of them for several months on the Pyrenean trekking trails GR10, GR11 and HRP. This multi-criteria approach allowed us to get to know them better, to understand their representations and motivations, as well as to update more general knowledge about mountain trekking and trekking in the high-altitude Pyrenees. We were finally able to see that “the possibilities of another look” on these mountains, driven in part by the difference in altitude with regard to the Alps, leads to a more contemplative practice and to seeking an adventure that is more linked to enjoying nature, seen here as wild, preserved and authentic.